Secured Real-Time Machine Communication Protocol - Ren, yifei; Rupasinghe, Lakmal; Khaksar, Siavash; Ferdosian, Nasim; Murray, Iain (2024)
In this paper, we introduce the Secured Real-Time Machine Communication Protocol (SRMCP), a novel industrial communication protocol designed to address the increasing demand for security and performance in Industry 4.0 environments. SRMCP integrates post-quantum cryptographic techniques, including the Kyber Key Encapsulation Mechanism (Kyber-KEM) and AES-GCM encryption, to ensure robust protection against both current and future cryptographic threats. We also present an innovative “Port Hopping” mechanism inspired by frequency hopping, enhancing security by distributing communication across multiple channels. Comparative performance analysis was conducted with widely-used protocols such as ModBus and the OPC UA, focusing on key metrics such as connection, reading, and writing times across local and remote networks. Results demonstrate that SRMCP outperforms ModBus in reading and writing operations while offering enhanced security, although it has a higher connection time due to its dual-layer encryption. The OPC UA, while secure, lags significantly in performance, making it less suitable for real-time applications. The findings suggest that SRMCP is a viable solution for secure and efficient machine communication in modern industrial settings, particularly where quantum-safe security is a concern.